Rational Design and Immunological Mechanisms of Circular RNA-Based Vaccines: Emerging Frontiers in Combating Pathogen Infection - Ying Zhang; Shumei Jin; Zan Zuo; Shujing Liu; Juan Xu; Chongyi Yang; Ping Wan; Linting Xun; Mei Luo; Fan Yang; Wenjie Chen; Zhengji Song; et al. (Vaccines)
Vaccines remain one of the most effective tools in combating infectious diseases, though traditional platforms are constrained by limitations including suboptimal immunogenicity, safety concerns, and manufacturing complexity. Circular RNA (circRNA) vaccines have recently emerged as a novel vaccine modality, demonstrating unique advantages including high stability, low innate immunogenicity, and sustained antigen expression. Although early research has predominantly focused on viral targets, accumulating evidence now supports the application potential of circRNA vaccines against diverse pathogens, particularly antibiotic-resistant bacteria. Through encoding critical antigens or virulence factors, these circRNA vaccines demonstrate capability to induce protective immune responses, presenting a viable alternative to conventional antimicrobial strategies. This review highlights recent advances in circRNA vaccine development, spanning synthetic circularization techniques, delivery approaches, and immunological mechanisms. We emphasize their potential against viral, bacterial, fungal, and parasitic infections, while addressing current challenges and future research directions of this emerging platform. Collectively, these insights underscore circRNA’s multifaceted versatility and its expanding relevance in next-generation vaccine innovation.